2023
DOI: 10.1117/1.jmi.10.s2.s22404
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning convolutional neural network-based scatter correction for contrast enhanced digital breast tomosynthesis in both cranio-caudal and mediolateral-oblique views

Abstract: Purpose: Scatter radiation in contrast-enhanced digital breast tomosynthesis (CEDBT) reduces the image quality and iodinated lesion contrast. Monte Carlo simulation can provide accurate scatter estimation at the cost of computational burden. A model-based convolutional method trades off accuracy for processing speed. The purpose of this study is to develop a fast and robust deep-learning (DL) convolutional neural network (CNN)-based scatter correction method for CEDBT.Approach: Projection images and scatter ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Furthermore, it was noted that the SR predictions from pCNN are smoother than the actual training targets, suggesting that CNN-based methods do not contribute additional noise to the reconstructed image. 30 The accuracy of SR predictions was further improved after TL (see Fig. 9).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, it was noted that the SR predictions from pCNN are smoother than the actual training targets, suggesting that CNN-based methods do not contribute additional noise to the reconstructed image. 30 The accuracy of SR predictions was further improved after TL (see Fig. 9).…”
Section: Discussionmentioning
confidence: 90%
“…[1][2][3][4] In conventional clinical situation, low-energy (LE) and high-energy (HE) images are acquired with two separate exposures, referred to as the dual-shot (DS) method in this study. [5][6][7][8][9][10] Patient motion between two exposures occurs frequently with DS method, which could result in residual breast tissue structure in recombined DE images, which impacts the image quality and iodinated lesion conspicuity. 5,[11][12][13][14][15][16][17][18] Studies have shown that for cases with gross patient motion, the artifact cannot be completely eliminated with image registration algorithms.…”
Section: Introductionmentioning
confidence: 99%